Ad libitum caffeine consumption, cognitive performance, and sleep in special forces soldiers during a 96-h combat exercise - Erez, David; Lieberman, Harris R.; Baum, Ido; Ketko, Itay; Moran, Daniel S. (Frontiers in Neuroscience, 2024)
This observational study investigated the effects of sleep deprivation and ad libitum caffeine consumption on cognitive performance, risk behavior, and mood among 28 Israeli Special Forces (SF) soldiers (mean age: 20.57±0.92 years) during a 96-hour combat exercise. Actigraphy was used to monitor sleep and activity; cognitive function, risk-taking propensity, mood states, and selfreported sleepiness were assessed using the Psychomotor Vigilance Task (PVT), Evaluation of Risks Scale (EVAR), Profile of Mood States (POMS), Karolinska Sleepiness Scale (KSS); and caffeine consumption by questionnaire at 0, 50, and 96 hours. For analyses, participants were divided into Low (<400 mg) and High (≥400 mg) caffeine consumption groups. The soldiers hiked 108.5±0.52 km and slept for 12.7±0.5 hours, with a notable transition from multiple short sleep epochs in the initial 50 hours to a consolidated 5-hour sleep period subsequently. In the High caffeine group, PVT reaction time was faster (p=0.024) compared to the Low caffeine group, with fewer premature response errors (p=0.026). However, this group showed increased risk-taking (p=0.037), particularly reduced Self-Control (p=0.010). No significant impact of ad libitum caffeine intake on mood was observed. However, degradation over the course of the exercise in both groups in mood states, including anger, fatigue, tension, and vigor, was noted (p<0.05). KSS scores increased significantly at 50 and 96 hours (p<0.001). These results suggest that while caffeine enhances cognitive function, its ad libitum consumption did not consistently improve these measures in this cohort of SF soldiers.The study highlights the complex relationship between sleep deprivation and caffeine intake and their combined effects on soldiers' cognitive and behavioral functions, indicating a need for evidencebased caffeine use guidelines for using caffeine in military settings.